Vascular Surgery - Davies, Alun H.; Brophy, Colleen M. (Springer Specialist Surgery Series, 2006)
Vascular Surgery is an essential aid for those who need a practical understanding of the procedure when preparing for surgery examinations. Edited by prominent vascular surgeons in the USA and UK, the book tackles the epidemiology and etiology of atherosclerosis and how to evaluate patients with vascular disease. Specific vascular diseases are then covered and their treatment options discussed. Vascular Surgery adopts a transatlantic approach so that chapters are written either by a practitioner in the USA or UK, and each chapter is critically appraised by a colleague who provides a potentially alternative perspective. This book is key reading for trainees in vascular surgery, as well as for surgery trainees in general. It would also be useful to those who have already qualified but might need further knowledge of this important field.